Recycling of Raw Materials, Silicon Wafers and Complete Solar Cells from Photovoltaic Modules (Journal of Solar Energy Research Updates, 2016)
Photovoltaic modules (PVs) are an attractive way of generating electricity in reliable and maintenance-free systems with the use of solar energy. The average lifetime of photovoltaic modules is 25 to 30 years. To offset the negative impact of photovoltaic modules on the environment, it is necessary to introduce a long-term strategy that includes a complete lifecycle of all system components from the production phase through installation and operation to disposal. Recycling of waste products and worn-out systems is an important element of this strategy. Environmental benefits of recycling are related not only to the limited space of landfills, but also to energy saving, raw materials and emission reduction. An important argument for the recycling of photovoltaic modules is the reduction of energy consumption at their production stage through the reuse of existing purified materials. The paper presents selected methods of recycling of used or destroyed PV modules and photovoltaic cells and the results of practical experiments.